2013
DOI: 10.1039/c2dt31737k
|View full text |Cite
|
Sign up to set email alerts
|

Functional group chemistry at intramolecular frustrated Lewis pairs: substituent exchange at the Lewis acid site with 9-BBN

Abstract: The vicinal frustrated P/B Lewis pair (FLP) Mes(2)PCH(2)CH(2)B(C(6)F(5))(2) reacts with 9-borabicyclo[3.3.1]nonane (9-BBN) by C(6)F(5)vs. H exchange at boron to give the new [B]-H functionalized FLP Mes(2)PCH(2)CH(2)B(H)(C(6)F(5)) (4) and 9-C(6)F(5)-BBN. The latter was characterized as an isonitrile adduct by X-ray diffraction. The new FLP 4 forms an adduct with pyridine and it undergoes clean hydroboration reactions with 1-pentyne or added styrene or dimesitylvinylphosphane. The products formed stable adducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…We also reported on the synthesis of the six‐membered P/B system 6 . This compound was obtained by twofold hydroboration of 1 with Piers’ borane and subsequent C 6 F 5 /hydride exchange by treatment with 9‐BBN (with formation of C 6 F 5 ‐BBN) and rearrangement. We have now used 6 to generate the free six‐membered ring P/B FLP system 7 (see Scheme ) and found that it exhibits remarkable behaviour, which is described in this account.…”
Section: Methodsmentioning
confidence: 99%
“…We also reported on the synthesis of the six‐membered P/B system 6 . This compound was obtained by twofold hydroboration of 1 with Piers’ borane and subsequent C 6 F 5 /hydride exchange by treatment with 9‐BBN (with formation of C 6 F 5 ‐BBN) and rearrangement. We have now used 6 to generate the free six‐membered ring P/B FLP system 7 (see Scheme ) and found that it exhibits remarkable behaviour, which is described in this account.…”
Section: Methodsmentioning
confidence: 99%
“…A class of compounds closely related to the Al/P FLPs contain Al or Ga and N atoms. Weak bonding interactions between the Lewis acidic metal and the Lewis basic N atoms result in strained four- [11][12][13][14] or three-membered heterocyles [15][16][17][18]. Cleavage of the relatively weak donor-acceptor bonds in the presence of suitable substrates results in a reactivity similar to that of FLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of frustration these compounds were named active Lewis pairs (ALPs) [11]. The exceptional and variable reactivity of these ALPs has been demonstrated by their reactions with isocyanates, nitriles, terminal alkynes, carbon dioxide, carbodiimide and other substrates [11][12][13][14][15][16][17][18]. Particularly noteworthy is their capability to oligomerize suitable monomeric starting materials such as cyanamides [12].…”
Section: Introductionmentioning
confidence: 99%
“…[3a] We also reported on the synthesis of the sixmembered P/B system 6. [4] This compound was obtained by twofold hydroboration of 1 with Piers borane [5] and subsequent C 6 F 5 /hydride exchange by treatment with 9-BBN (with formation of C 6 F 5 -BBN) [6] and rearrangement. We have now used 6 to generate the free six-membered ring P/B FLP system 7 (see Scheme 2) and found that it exhibits remarkable behaviour,w hich is described in this account.…”
mentioning
confidence: 99%
“…Aview of the cyclooctameric ring structure (7) 8 (thermal ellipsoids are shown at 15 %p robability). [17] Hydrogen atoms are omitted and only the connecting carbon atoms of the bulky C 6 , and determined their free-energy content relative to that of the monomer 7.T he cyclooctamer (7) 8 was the only cyclic supramolecular structure that we could locate as am inimum structure on this hypersurface.W efound no other macrocyclic supra-structure of significant stability,b ut there were several open-chain structures that represented thermally accessible local minima (Figure 3). According to our DFT analysis,the monomer 7 is the energetically favored structure in CH 2 Cl 2 solution at 298 K. Theo ligomers fall in as mall free-energy window of about 2kcal mol À1 and thus,lowering the temperature leads to increasingly favouring the aggregated structure.T his aggregation is attributed to ad ecrease of the entropic penalty for cyclic aggregation.…”
mentioning
confidence: 99%